"I STOPPED SMOKING." GRANDPARENT CAREGIVERS' SELF-CARE PRACTICES FOLLOWING AN INTERVENTION. (11th November 2018) - Fruhauf, C; Mendoza, N; Greenwood-Junkermeier, H; Carson, J; Sanchez, G; Spencer, C; Yancura, L; Riggs, N
Abstract: Grandparents raising grandchildren experience greater physical health declines and higher rates of depression, than their age-related peers who do not provide care. Although this is well known, few researchers have examined the impact of self-care programming on decreasing negative outcomes in grandparents raising grandchildren. This study used a version of the Powerful Tools for Caregivers (PTC) program, adapted for grandparents raising grandchildren, to examine health behavior change among a sample of 59 grandparents from Colorado and Hawai'i. The ages of the grandparents ranged from 46 to 83 (M = 62.38) years old, and 52 participants were grandmothers. A majority (n = 25; 42%) of grandparents were raising one grandchild with a total of 18 (30%) grandparents raising two grandchildren. The purpose of this presentation is to describe findings from five focus groups and one interview conducted with 16 grandparents, six months after completing the 6-week self-care intervention. Focus groups were tape recorded and transcribed. Transcripts were coded for content related to positive behavior change and grandparents' self-care practices. Results indicate that grandparents reported making positive changes in: (1) taking time for themselves, (2) reducing negative self-talk, (3) increasing healthy physical choices, and (4) better communication with family members. These findings, 6-months after the completion of the program, are similar to findings from participants (i.e., caregivers for adults with chronic disease) in the original PTC program. This suggests that that the adapted version of this program shows similar promise to the original for improving the health of grandparent caregivers.